ANALISIS KESESUAIAN STANDAR MUTU BUKU TEKS BAHASA INDONESIA KELAS X DENGAN IKM DI MAN SUKOHARJO - Febriyanti, Dhini; Mulyawati, Ika Martanti (Universitas Madura, 2023)
This study aims to describe the suitability of the textbook Cerdas Cerdas Cergas Berbahasa dan Bersastra Indonesia for SMA/SMK Class X with the textbook quality standards according to BSKAP and find out the IKM with textbooks at MA Negeri Sukoharjo. The method used is descriptive qualitative. The source of the data comes from the textbook Cerdas Cergas Berbahasa dan Bersastra Indonesia SMA/SMK Class X, Indonesian language teachers, vice principal for curriculum, and grade X students of MA Negeri Sukoharjo. The results of the research found a total of 238 data. Data from the book in the form of text as much as 72 data, images as much as 58 data, and links or QR codes as much as 11 data. This textbook is quite feasible to use as teaching material according to the textbook criteria stipulated in Permendikbudristek Numb. 22 of 2022 concerning Book Quality Standards, Process Standards and Manuscript Acquisition Rules, and Process Standards and Book Publishing Rules. It is said to be quite feasible because only five errors were found. Namely sentenceineffectiveness, inconsistency of writing, writing errors, uneven ink, dan the appearance of electronic book images look blurry. The interview data contained the role of the independent curriculum in MA 18 data, the application of IKM learning to textbooks 32 data, and student responses to textbooks 47 data. IKM with textbooks at MA Negeri Sukoharjo has been implemented, but not maximized. This textbook can be used as teaching material and the implementation of an independent curriculum is already underway, but evaluation needed.